2019
DOI: 10.31393/bba34-2019-03
|View full text |Cite
|
Sign up to set email alerts
|

Correlations of indices of personality traits with indexes of finger and palmar dermatoglyphics of practically healthy Ukrainian men

Abstract: The search for new psychodermatoglyphic correlations will greatly increase the possibilities of this method and will accelerate the introduction of scientific developments into the daily practice of clinicians, criminologists, police and other specialties. The purpose of the work is to establish the peculiarities of the relationship between the indexes of the finger and palmar dermatoglyphics and the characteristics of the personality traits of practically healthy Ukrainian men. From the data bank of the mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…The results of the quantitative analysis of correlations revealed the inverse relationships between the indicators of finger dermatoglyphics and indicators of personality traits according to Eysenck and Luscher, direct according to Spielberger, Schmischek and Rotter. In the analysis of palmar indicators of dermatoglyphics -feedback correlations with personality indicators according to Spielberger and Luscher and direct with indicators according to Eysenck, Schmishek and Rotter [11,26].…”
Section: Discussionmentioning
confidence: 99%
“…The results of the quantitative analysis of correlations revealed the inverse relationships between the indicators of finger dermatoglyphics and indicators of personality traits according to Eysenck and Luscher, direct according to Spielberger, Schmischek and Rotter. In the analysis of palmar indicators of dermatoglyphics -feedback correlations with personality indicators according to Spielberger and Luscher and direct with indicators according to Eysenck, Schmishek and Rotter [11,26].…”
Section: Discussionmentioning
confidence: 99%
“…Analyzing the features of correlations between cardiointervalographic parameters and indicators of external body structure in mesomorphic volleyball players, it is necessary to note the smaller number and strength of the identified reliable relationships, in contrast to the group of fighters who also belonged to this somatotype, as noted in our previous studies [24]. In addition, it was found that volleyball players of mesomorphic somatotype had more numerous correlations between variations of heart rate and spectral parameters of heart rate variability and indicators of external body structure than athletes, who also belonged to this constitutional type [20].…”
Section: Discussionmentioning
confidence: 56%
“…Spectral indices of mesomorphic type wrestlers, which in athletes [18], were found to have the least significant correlation with external body size compared to other cardiointervalographic parameters.…”
Section: Discussionmentioning
confidence: 82%
“…Analyzing the peculiarities of correlations between cardiointervalographic parameters and indicators of external body structure in mesomorph wrestlers, it is necessary to note a much greater number and strength of revealed reliable relationships, unlike the group of athletes who also belonged to this somatotype, as noted in our previous studies [18]. In addition, it was found that the wrestlers of the mesomorphic somatotype had more numerical correlations between the femur rheographic parameters and constitutional characteristics than the athletes [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation